2018
DOI: 10.1051/swsc/2018021
|View full text |Cite
|
Sign up to set email alerts
|

Climate, weather, space weather: model development in an operational context

Abstract: -Aspects of operational modeling for climate, weather, and space weather forecasts are contrasted, with a particular focus on the somewhat conflicting demands of "operational stability" versus "dynamic development" of the involved models. Some common key elements are identified, indicating potential for fruitful exchange across communities. Operational model development is compelling, driven by factors that broadly fall into four categories: model skill, basic physics, advances in computer architecture, and ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…ESMs can be distinguished from global climate models by their ability to simulate the carbon cycle and by the sophistication of their atmospheric and oceanic chemistry (Heavens et al., 2013), in an NWP mode (See Section 4.3). The rationale is that climate can be considered as the long‐term statistical average of weather, and therefore, a good climate model must also manifest good NWP properties (Folini, 2018). As the atmospheric component of the ESM is validated against detailed (pseudo‐)observational data, there is more confidence in the physical ground.…”
Section: Ensemble Streamflow Forecasting: Success Challenges and Futu...mentioning
confidence: 99%
“…ESMs can be distinguished from global climate models by their ability to simulate the carbon cycle and by the sophistication of their atmospheric and oceanic chemistry (Heavens et al., 2013), in an NWP mode (See Section 4.3). The rationale is that climate can be considered as the long‐term statistical average of weather, and therefore, a good climate model must also manifest good NWP properties (Folini, 2018). As the atmospheric component of the ESM is validated against detailed (pseudo‐)observational data, there is more confidence in the physical ground.…”
Section: Ensemble Streamflow Forecasting: Success Challenges and Futu...mentioning
confidence: 99%
“…The development of the latter is not an easy task. Building a bridge between research and operations and effective research-to-operations transfer are identified as some of the key challenges (Araujo-Pradere, 2009;Folini, 2018;Merceret et al, 2013). Furthermore, the development of operationally oriented physics-based numerical models, in particular Sun-to-Earth simulations, requires significant computational effort.…”
Section: Introductionmentioning
confidence: 99%